2020
DOI: 10.1155/2020/8857669
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Volatile Essential Oils of Myrtle (Myrtus communis L.) Leaves for Improving the Postharvest Storability of Fresh Loquat Fruits

Abstract: Fresh loquat (Eriobotrya japonica Lindl.) fruits easily lose their marketability because of fungal spoilage, browning, and weight loss after harvest. The use of essential oils as postharvest treatment is a talented alternative to fungicides mainly because of their ability to reduce respiration and transpiration of the fresh fruits during storage. However, the postharvest studies with the volatiles of essential oils are limited. The present study was conducted to determine the effectiveness of volatile essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Hereafter, the quality of control fruits had rapidly decreased while both doses of P. rhoeas fruit extracts had prevented this reduction. In a different study, it was also reported that essential oils of myrtle improve visual quality and reduce browning of the loquat fruits (Bahadırlı et al, 2020). Chilling injury results had been found to be similar with the visual quality results (See Figure 2D).…”
Section: Effects On Physical Quality Parameterssupporting
confidence: 59%
See 1 more Smart Citation
“…Hereafter, the quality of control fruits had rapidly decreased while both doses of P. rhoeas fruit extracts had prevented this reduction. In a different study, it was also reported that essential oils of myrtle improve visual quality and reduce browning of the loquat fruits (Bahadırlı et al, 2020). Chilling injury results had been found to be similar with the visual quality results (See Figure 2D).…”
Section: Effects On Physical Quality Parameterssupporting
confidence: 59%
“…In our study, the fruit extracts of P. rhoeas provided better performance than nanochitosan emulsion coatings and maintained the weight loss around 10% in 30 days of storage. Moreover, Bahadırlı et al (2020) suggested that the essential oils of myrtle (Myrtus communis L.) provide similar performance in preventing weight loss of loquat fruits. Although the test materials are different, overall results and discussion with the existing available information suggests that fruit extracts of P. rhoeas have significant impact on the prevention of weight loss at apricot fruits.…”
Section: Effects On Physical Quality Parametersmentioning
confidence: 99%
“…Eucalyptol is a major compound of the chemical composition of several herbs including basil, myrtle, sage, rosemary, thyme and etc. (Bahadırlı et al 2020;Puvača et al 2021). It is also reported to have a significant role in the antifungal and antioxidant activities of the oils (Mogoşanu et al 2017).…”
Section: Chemical Composition Of the Laurel Essential Oilsmentioning
confidence: 97%
“…Gas chromatography-mass spectrometry (GC-MS) method with Thermo Scientific ISQ Single Quadrupole device was used for analyzing the compounds of essential oils. The method described by Bahadırlı et al (2020) was followed for…”
Section: Determination Of Essential Oil Compoundsmentioning
confidence: 99%
“…The application of the EOs can be as direct application (as vapor) or incorporation into films, coatings or washing materials [41]. Some recent research noted that the essential oils of myrtle (Myrtus communis L.) leaves [129], black cumin oil [130], and lemongrass oil [131] have high potential of promoting storability of loquat, apricot and strawberry fruits, respectively.…”
Section: Essential Oils Application To Stored Fruitsmentioning
confidence: 99%